Hypoxia: syndicating triple negative breast cancer against various therapeutic regimens - Srivastava, Nityanand; Usmani, Salman Sadullah; Subbarayan, Rajasekaran; Saini, Rashmi; Pandey, Pranav Kumar (Frontiers in Oncology, 2023)
Triple-negative breast cancer (TNBC) is one of the deadliest subtypes of breast cancer (BC) for its high aggressiveness, heterogeneity, and hypoxic nature. Based on biological and clinical observations the TNBC related mortality is very high worldwide. the Emerging studies have clearly demonstrated that hypoxia regulates the critical metabolic, developmental, and survival pathways in TNBC, which include glycolysis and angiogenesis. Alterations to these pathways accelerate the cancer stem cells (CSCs) enrichment and immune escape, which further lead to tumor invasion, migration, and metastasis. Beside this, hypoxia also manipulates the epigenetic plasticity and DNA damage response (DDR) to syndicate TNBC survival and its progression. Hypoxia fundamentally creates the low oxygen condition responsible for the alteration in HIF1-alpha (HIF-1) signaling within the tumor microenvironment, allowing tumors to survive and making them resistant to various therapy regimens. Therefore, there is an urgent need for society to establish target-based therapies that overcome the resistance and limitations of the current treatment plan for TNBC. In this review article, we have thoroughly discussed the plausible significance of HIF-1α as a target in various therapeutic regimens such as chemotherapy, radiotherapy, immunotherapy, anti-angiogenic therapy, as well as adjuvant and photodynamic therapy. Further, we also reviewed here the intrinsic mechanism and existing issues in targeting HIF-1α while improvising the current therapeutic strategies. This review highlights and discusses the future perspectives and the major alternatives to overcome TNBC resistance by targeting hypoxia-induced signaling.